Kandungan Protein, Kekerasan Dan Daya Terima Cookies Tepung Komposit Sagu Baruk (Arenga microcarpa) Dan Kacang Hijau (Vigna radiata) - Hariyati Lasaji; Jan Rudolf Assa; Mercy I. R. Taroreh (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The purpose of this study was to evaluate the protein content, hardness and acceptability of cookies with sago Baruk and mung bean composite flour. This study used the CRD method (Completely Randomized Design), which consisted of 4 treatments and 3 repetitions as follows: F0 sago baruk flour 100%:0% mung bean flour, F1 sago baruk flour 70%:30% mung bean flour, F2 sago baruk flour 60%:40% mung bean flour and F3 sago baruk flour 50%:50% mung bean flour. Then the protein content analysis, hardness and acceptability test were carried out. The results of this study indicate that the composite flour cookies of sago baruk and mung bean yielded protein content, namely F0 obtained a value of 2.77%, F1 obtained a value of 8.33%, F2 obtained a value of 10.17% and F3 obtained a value of 11.86%. The study also showed that the hardness of cookies with composite flour of sago Baruk and green beans were F0 with a value of 6656.16 gf, F1 with a value of 5028.33 gf, F2 with a value of 3983.57 gf and F3 with a value of 3531.11 gf. Based on the panelists' response to the level of preference for cookies, the composite flour of sago baruk and mung bean with the most preferred response by the panelists was a mixture of 70% sago baruk flour and 30% mung bean flour which had a color preference value of 3.75 (like), taste 4.01 (likes), aroma 3.59 (likes), texture 4.07 (likes) with a protein content of 8.33%, water content of 3.65% and a hardness level of 5028.33 gf. Keywords: Cookies; Sago Baruk; Mung Bean; Protein, Hardness.